Public Management of Employment at the Level of Territorial Communities in the Context of Ensuring the Development of Rural Areas - Babaiev, Valerij; Babaieva, Iryna (Theory and Practice of Public Administration, 2022)
United territorial communities were formed by voluntary unification of adjacent territorial communities of villages, towns, and cities. The availability, working conditions, and the level and quality of life of the population of rural communities significantly affect the development possibilities of rural areas. Problematic issues are the growth of unemployment, the demographic crisis, the intensive outflow of young people from the countryside, etc. The primary issue for anti-crisis public administration in rural areas (at the level of rural territorial communities and rural districts) is ensuring employment and self-employment of the population, increasing the level of labor income of the rural population. The low capacity of the labor market in rural territorial communities determines the need for the population to find work outside their place of residence and, in this connection, the presence of significant financial costs. The introduction of new types of activities and areas of employment for residents of the rural community must meet the needs of the market and be economically feasible, because otherwise public policy measures to support such types of employment will have a short-term nature and insignificant results. The tools of the public employment policy are: unemployment benefits, insurance of the population against job loss; assistance in professional training and retraining of personnel, conducting advanced training courses, organization and regulation of labor exchanges, public employment services; regulation of the wage level, regularization of the dismissal of employees; subsidies and benefits from tax accounting for entrepreneurs, regarding the creation of new and preservation of old jobs. Public management of employment at the level of the territorial community should be aimed at ensuring the possibility of effective economic activity of the residents of the community. At the same time, they should receive sufficient financial support to motivate work. This requires: creation of procurement points with a wide range of products with the participation of territorial communities; combining them into a procurement network; active cooperation with public administration bodies; networks of procurement points to international supply chains; ensuring their access to foreign food markets.